2007
DOI: 10.1158/1055-9965.epi-06-0756
|View full text |Cite
|
Sign up to set email alerts
|

What Do Women in the U.S. Know about Human Papillomavirus and Cervical Cancer?

Abstract: Background: Women need to understand the link between human papillomavirus (HPV) and cervical cancer in order to make appropriate, evidence-based choices among existing prevention strategies (Pap test, HPV DNA test, and HPV vaccine). Assessment of the public's knowledge in nationally representative samples is a high priority for cervical cancer control. Objectives: To assess factors associated with U.S. women's awareness of HPV and knowledge about its link to cervical cancer. Methods: Analyzed cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

28
143
5
9

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 199 publications
(185 citation statements)
references
References 41 publications
(62 reference statements)
28
143
5
9
Order By: Relevance
“…White caregivers and those with some college education had higher HPV knowledge. Our findings are consistent with studies that identified racial differences in awareness and knowledge of HPV, the HPV vaccine, and cervical cancer (13,14,24). Studies have also found awareness of HPV to be lower among the less educated and higher among non-Hispanic Whites (13,14).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…White caregivers and those with some college education had higher HPV knowledge. Our findings are consistent with studies that identified racial differences in awareness and knowledge of HPV, the HPV vaccine, and cervical cancer (13,14,24). Studies have also found awareness of HPV to be lower among the less educated and higher among non-Hispanic Whites (13,14).…”
Section: Discussionsupporting
confidence: 92%
“…Despite the proven efficacy of HPV vaccines and a surge in media coverage of cancer-related topics in recent years, past research suggests that this new prevention strategy is little understood by the public (12)(13)(14)(15). A review of seven studies found that 58% of respondents had never heard of HPV (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies to enforce the knowledge of HPV transmission, prevention, detection as well as risk and management of cervical neoplasia are necessary for all societies. 31 Our cross-sectional results showed that the improvement of sensitivity with additional HPV testing was only 15.3%. The whole project is still ongoing to evaluate safety and cost-effectiveness of screening with Pap plus HPV testing at longer intervals, which can be answered after longterm follow-up.…”
Section: Discussionmentioning
confidence: 65%